Three novel Ambrosia Fusarium Clade species producing multiseptate "dolphin-shaped" conidia, and an augmented description of Fusarium kuroshium. (3rd September 2021) - Aoki, Takayuki; Liyanage, Pradeepa N. H.; Konkol, Joshua L.; Ploetz, Randy C.; Smith, Jason A.; Kasson, Matt T.; Freeman, Stanley; Geiser, David M.; O'Donnell, Kerry
ABSTRACT: The Ambrosia Fusarium Clade (AFC) is a monophyletic lineage within clade 3 of the Fusarium solani species complex (FSSC) that currently comprises 19 genealogically exclusive species. These fungi are known or predicted to be farmed by adult female Euwallacea ambrosia beetles as a nutritional mutualism (Coleoptera: Scolytinae; Xyleborini). To date, only eight of the 19 AFC species have been described formally with Latin binomials. We describe three AFC species, previously known as AF-8, AF-10, and AF-11, based on molecular phylogenetic analysis of multilocus DNA sequence data and comparative morphological/phenotypic studies. Fusarium duplospermum (AF-8) farmed by E. perbrevis on avocado in Florida, USA, is distinguished by forming two morphologically different types of multiseptate conidia and brownish orange colonies on potato dextrose agar (PDA). Fusarium drepaniforme (AF-10), isolated from an unknown woody host in Singapore and deposited as Herb IMI 351954 in the Royal Botanic Gardens, Kew, UK, under the name F. bugnicourtii, is diagnosed by frequent production of multiseptate sickle-shaped conidia. Fusarium papillatum (AF-11), isolated from mycangia of E. perbrevis infesting tea in Kandy, Sri Lanka, forms multiseptate clavate conidia that possess a papillate apical cell protruding toward the ventral side. Lastly, we prepared an augmented description of F. kuroshium (AF-12), previously isolated from the heads or galleries of E. kuroshio in a California sycamore tree, El Cajon, California, USA, and recently validated nomenclaturally as Fusarium . Conidia formed by F. kuroshium vary widely in size and shape, suggesting a close morphological relationship with F. floridanum, compared with all other AFC species. Maximum likelihood and maximum parsimony analyses of a multilocus data set resolve these three novel AFC species, and F. kuroshium, as phylogenetically distinct based on genealogical concordance. Given the promiscuous nature of several Euwallacea species, and the overlapping geographic range of several AFC species and Euwallacea ambrosia beetles, the potential for symbiont switching among sympatric species is discussed.